Liver-boosting potential: chicory compound-mediated silver nanoparticles for hepatoprotection—biochemical and histopathological insights - Siddiqa, Ayesha; Qureshi, Rahmatullah; Raja, Naveed Iqbal; Khan, Imtiaz Ahmed; Ahmad, Muhammad Zishan; Rafique, Shaista; Ali, Amir; Ahmad, Ajaz; Kaushik, Prashant (Frontiers in Pharmacology, 2024)
Liver disease is a serious health concern in today's world, posing a challenge to both healthcare providers and pharmaceutical companies. Most synthetic drugs and chemicals cause liver damage counting for approximately 10% of acute hepatitis and 50% of acute liver failures. The present study aimed to evaluate the hepato-protective activity of an extract of chicory formulation assisted with silver nanoparticles against carbon tetra chloride induced hepatic damage in rat’s liver. Silver nanoparticles were synthesized and characterized, in vivo hepato-protective activity was performed using rats of the Wistar strain (Rattus norvegicus) in different concentrations. Rats were randomly divided into nine groups, each containing six rats. The 1st group (control), 2nd group (CCl4), 3rd group Silymarin (20 mg/kg of body weight), 4th group (CCl4+Chicory (1.75 mg/kg of b. wt), 5th group (CCl4 + Chicory at the dose of 2.35 mg/kg), 6th group (CCl4 + Chicory of 3.25 mg/kg), 7th group (CCl4 +AgNPs 1.75 mg/kg of b. wt.), 8th group (CCl4 + AgNPs 2.35 mg/kg of body weight), 9th group (CCl4 + AgNPs 3.25 mg/kg of b. wt.). Blood samples were taken 24 hours after the last administration (30th day). The blood samples were analyzed for different serum enzymes such as ALP (alkaline phosphatase), ALT (alanine transaminase), bilirubin, triglyceride, and cholesterol. Histology liver sections were performed. Treatment with AgNPs and chicory extract showed significant hepato-protective activity in a dose-dependent manner. The three doses, the chicory extract at rate of 3.25 mg/kg of body weight significantly reduced elevated levels of biochemical markers in comparison to CCl4-intoxicated rats. Histology of the liver sections from CCl4-treated rats revealed inflammation of hepatocytes, necrosis, cytoplasmic degeneration, vacuolization, and a deformed central vein. The chicory formulation extract exhibited a remarkable recovery percentage in the liver architecture that was higher than the drug (silymarin). While treatment with AgNPs also repaired the degenerative changes and restored the normal form of the liver, cchicory formulationextract possessed more hepato-protective potential as compared to AgNPs by regulating biochemical and histo-pathological parameters. This study may be used to establish the hepato-protective potential of chicory compounds for possible use in drug development programs against liver diseases.